(untitled) (Revista Científica Integrada, 2025)
Objective: Analyze maternal deaths and deaths from abortions of women of reproductive age in Brazil between 2015 and 2023. Method: A cross-sectional, descriptive and exploratory population-based study, with data extracted from the TabNet database of the Brazilian National Health System (DATASUS). Maternal deaths whose cause was categorized as abortion (ICD-10 O003 to O07) were included. Incomplete data was excluded. Descriptive analysis included demographic and social variables, and EPI-INFO 7.2® software was used for statistical calculations. Results: There was a higher concentration of deaths among women aged 40-49, with a predominance of maternal deaths in the 30-39 age group. Brown and single women were the most affected. The Southeast had the highest number of deaths, followed by the Northeast. Deaths in hospitals predominated, but deaths also occurred in homes and other places. Infectious and hemorrhagic complications were frequent in abortion cases. Conclusion: The data reveal regional and racial inequalities in maternal mortality, as well as highlighting the vulnerability of women with low levels of schooling and limited family support. The analysis emphasizes the need for public policies to improve access to reproductive health care and the importance of interventions targeting specific groups to reduce maternal mortality in Brazil. Keywords: Abortion; Women’s Health; Mortality; Maternal Mortality; Information Systems